2023
DOI: 10.1186/s12951-023-01818-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced mild-temperature photothermal therapy by pyroptosis-boosted ATP deprivation with biodegradable nanoformulation

Abstract: Background Mild-temperature photothermal therapy (mild PTT) is a safe and promising tumor therapeutic modality by alleviating the damage of healthy tissues around the tumor due to high temperature. However, its therapeutic efficiency is easily restricted by heat shock proteins (HSPs). Thus, exploitation of innovative approaches of inhibiting HSPs to enhance mild PTT efficiency is crucial for the clinical application of PTT. Results Herein, an innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…This is a sign that the cells were undergoing the phenomenon of pyroptosis (Figure S35, Supporting Information). [ 27 ] Our first thought was that copper ions overloading led to osmotic swelling of the cells, which then resulted in pyroptosis. To verify this speculation, we cultured 4T1 cells in medium containing CuCl 2 (Cu 2+ concentration range of 32–320 µg mL −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is a sign that the cells were undergoing the phenomenon of pyroptosis (Figure S35, Supporting Information). [ 27 ] Our first thought was that copper ions overloading led to osmotic swelling of the cells, which then resulted in pyroptosis. To verify this speculation, we cultured 4T1 cells in medium containing CuCl 2 (Cu 2+ concentration range of 32–320 µg mL −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The combination of decreased ATP and accumulated ROS synergistically inhibited the levels of HSPs, leading to significant mPTT effects. [ 128 ] The combination of pyroptosis and mPTT offers a promising strategy for cancer therapy, as it involves rapid cell death, the release of pro‐inflammatory factors, and the inhibition of HSPs, all of which contribute to effective tumor ablation. This approach represents a novel and potentially powerful method in the field of cancer treatment.…”
Section: Nanomedicine Mediated Mpttmentioning
confidence: 99%
“…[68] Mild PTT also offers the possibility of avoiding the damage of high temperatures to paracancerous tissues mitochondrial dysfunction and inducing pyroptosis. [66] Several studies have demonstrated that epigenetics may [33][34][35][36] Copyright 2023, The Royal Society of Chemistry. Copyright 2021, Wiley-VCH GmbH.…”
Section: The Polymer Prodrug Of Inducing Pyroptosismentioning
confidence: 99%
“…[ 68 ] Mild PTT also offers the possibility of avoiding the damage of high temperatures to paracancerous tissues mitochondrial dysfunction and inducing pyroptosis. [ 66 ] Several studies have demonstrated that epigenetics may influence the expression of GSDME, and a complex biGC@PNA combining radiofrequency‐responsive nanoparticles with epigenetic drugs can activate pyroptosis by noninvasive radiofrequency downstream, showing promising immunotherapeutic effects (Figure 8c). [ 63 ]…”
Section: The Application Of Biomaterials Induced Pyroptosis In Cancer...mentioning
confidence: 99%